Evaluasi Penerapan Harga Transfer di PT Reebonz - Ade Suryana (Institut Ilmu Sosial dan Manajemen Stiami, 2021)
This study aims to evaluate the transfer pricing activities of the transfer pricing practice conducted by PT Reebonz (“PT RB”) and its affiliates which are companies operating in a country with a lower tax rate than Indonesia in connection with compliance with the arm's length principle. This evaluation is carried out by analyzing the price setting which is measured based on Transactional Net Margin Method (TNMM) of independent comparison companies with the characteristics of similar industries to be compared with the net margin of PT RBI. This study used a qualitative method with a case study approach with data collection methods using interviews and documentation of data obtained from PT RB and data collection from the Bureau Van Dijk (